Unconditionally stable Crank-Nicolson wave-equation PML formulations for truncating FDTD domains - Ramadan, Omar; Oztoprak, Abdullah Y. (Springer, 2006)
Efficient, accurate and unconditionally stable perfectly matched layer (PML) formulations are presented for truncating Finite Difference Time Domain grids. The formulations are based on incorporating the Crank-Nicolson scheme into the modified Helmholtz wave-equation derived in the PML re-ion. Numerical example carried out in onedimension is included to validate the proposed formulations.
Keywords: Crank-Nicolson; finite difference time domain; perfectly matched layer; propagating waves; Maxwell's equations